COVID-19-related worries and mental health: the protective role of sense of coherence - Anita Padmanabhanunni; Serena Ann Isaacs; Tyrone B. Pretorius (Cogent Psychology)
Background: Much of the literature related to mental health focuses on identifying risk factors and predictors of poor mental health. Less of the research has a health-promoting orientation, focusing on potential sources of resilience and strength.Aims: The current study contributes to the growing field of positive psychology by investigating the potential protective role of sense of coherence (SOC) in the association between COVID-19-related worries and adverse mental health outcomes.Methods: Participants were South African undergraduate students (n = 337) who completed the SOC scale, COVID-19-related worries scale, Beck hopelessness scale, Center for Epidemiological Studies depression scale, and the trait scale of the state-trait anxiety inventory. We used the PROCESS macro for SPSS to examine the mediating role of SOC in the relationship between COVID-19-related worries and indices of mental health. The study was undertaking in the first and second waves of the COVID-19 disease outbreak in 2020.Results: T-test analyses found that women reported higher levels of depression and anxiety than men, and correlational analyses found a significant negative association between age and anxiety. After controlling for the confounding effects of age and gender, mediation analysis demonstrated that SOC had a direct and mediating effect on hopelessness, depression, and anxiety, suggesting that it is a potential protective resource. SOC is thus the pathway through which COVID-19-related worries impact mental health.Conclusion: Enhancing this resilience resource among vulnerable population groups can promote effective coping in the context of societal crises.